2008
DOI: 10.1111/j.1365-2826.2007.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of AMP‐Activated Kinase Activation on Gonadotrophin‐Releasing Hormone Secretion in GT1‐7 Cells and its Potential Role in Hypothalamic Regulation of the Oestrous Cyclicity in Rats

Abstract: Hypothalamic AMP-activated kinase (AMPK) is a key regulator of food intake in mammals. Its role in reproduction at the central level and, more precisely, in gonadotrophin-releasing hormone (GnRH) release has never been investigated. We showed that each subunit of AMPK is present in immortalised GnRH neurones (GT1-7 cells). Treatment with 5-aminoimidazole-4-carboxamide-1-beta-D-ribonucleoside (AICAR) and metformin, two activators of AMPK, increased dose-dependent and time-dependent phosphorylation of AMPKalpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 67 publications
(81 reference statements)
2
32
0
Order By: Relevance
“…It is worth noting, however, that direction-appropriate changes in AMPK activity (i.e. increase or decrease in activity) have been reported for both AICAR and compound C, that alterations in AMPK activity by one drug are antagonized by the other, and that each pharmacological agent is widely used to examine AMPK-mediated effects both in vivo and in vitro (20,21,41,43,(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting, however, that direction-appropriate changes in AMPK activity (i.e. increase or decrease in activity) have been reported for both AICAR and compound C, that alterations in AMPK activity by one drug are antagonized by the other, and that each pharmacological agent is widely used to examine AMPK-mediated effects both in vivo and in vitro (20,21,41,43,(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 98%
“…Activation of AMPK in the hypothalamus by the AMPK activator 5-aminoimidazole-4-carboxamide-1-b-D-ribofuranoside (AICAR) has been shown to stimulate phosphorylation of AMPK and ACC as well as upregulating expression of NPY and AgRP (Coyral-Castel et al 2008;Shimizu et al 2008). Molecular and pharmacological inhibition of hypothalamic AMPK decreases hepatic glucose production (Yang et al 2010).…”
Section: Ampk and Its Role In Food Intakementioning
confidence: 99%
“…In dispersed primary rat hypothalamic neuronal cell cultures, metformin inhibited PRKA activity in hypothalamic neurons, thus modulating the expression of the orexigenic peptide NPY [18]. Our laboratory has also shown that metformin inhibits gonadotropin-releasing hormone (GnRH) release from immortalized hypothalamic GT1-7 cells via PRKA activation, whereas compound C (Comp C), a well-known PRKA inhibitor, completely eliminates this effect [19]. Furthermore, adiponectin has been shown to reduce LH secretion in pituitary gonadotrophs in a PRKAdependent manner [20].…”
Section: Introductionmentioning
confidence: 94%